It's OK to be angry about capitalism [large type] - Sanders, Bernard; Nichols, John, 1959- (Random House Large Print, 2023)
The U.S. senator and former presidential candidate offers a progressive takedown of the uber-capitalist status quo that has enriched millionaires and billionaires at the expense of the working class, and presents a blueprint for what transformational change would actually look like.